(untitled) (Journal of Civil Engineering Researchers, 2020)
Structural control can be classified as active, semi-active and inactive. The main purpose of the passive control system is to reduce the participation of the main structural elements in the loss of input energy by plastic deformation. Delivery metal dampers, despite their simplicity, as structural control systems, offer special features such as economic efficiency without the need for advanced technology or expertise to build and install the system. The shear wall of a self-propelled steel plate is a lateral force-resistant system that can be replaced with steel filler plates by providing system return and limiting ductility. In the present study, it was tried to determine the characteristics and achievements obtained by evaluating four new and valid researches in order to evaluate the research of structural control systems including metal (modern) dampers and self-centered steel shear wall. The results of the present study showed that the use of metal damping system (composite, grooved and passive) and self-centered steel shear wall caused the reduction of plastic damage in columns and beams. Also, the amount of floor drift and shear axial force have a relatively large reduction. Also, due to the high cost of building construction, the use of these devices reduces the economic value of building construction.